Treatment of low-grade gastric MALT lymphoma using Helicobacter pylori eradication - Grgov, Saša; Katić, Vuka; Krstić, Miljan; Nagorni, Aleksandar; Radovanović - Dinić, Biljana; Tasić, Tomislav (Vojnosanitetski pregled, 2015)
Background/Aim. Lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) of the stomach usually occurs as a consequence of Helicobacter pylori (H. pylori) infection. The aim of this study was to investigate the long-term effect of treatment of low-grade gastric MALT lymphoma with the H. pylori eradication method. Methods. In the period 2002–2012 in 20 patients with dyspepsia, mean age 55.1 years, the endoscopic and histologic diagnosis of gastric MALT lymphoma in the early stages were made. Histological preparations of endoscopic biopsy specimens were stained with hematoxyllin-eosin (HE), histochemical and immunohistochemical methods. Results. Endoscopic findings of gastritis were documented in 25% of the patients, and 75% of the patients had hypertrophic folds, severe mucosal hyperemia, fragility, nodularity, exulcerations and rigidity. Histopathologically, pathognomonic diagnostic criterion were infiltration and destruction of glandular epithelium with neoplastic lymphoid cells, the so-called lymphoepithelial lesions. In all 20 patients H. pylori was verified by rapid urease test and Giemsa stain. After the triple eradication therapy complete remission of MALT lymphoma was achieved in 85% of the patients, with no recurrence of lymphoma and H. pylori infection in the average follow-up period of 48 months. In 3 (15%) of the patients, there was no remission of MALT lymphoma 12 months after the eradication therapy. Of these 3 patients 2 had progression of MALT lymphoma to diffuse large-cell lymphoma. Conclusion. Durable complete remission of low-grade gastric MALT lymphoma is achieved in a high percentage after eradication of H. pylori infection, thus preventing the formation of diffuse large-cell lymphoma and gastric adenocarcinoma.
Keywords: lymphoma; b-cell; marginal zone; stomach neoplasms; helicobacter pylori; drug therapy; remission induction; prognosis; histology